The Relationship Between Organizational Culture and Performance: A Review of Theory and Practice - Irfan, Mochamad; Al-Hakim, Yusuf Rahman; Sigita, Dwi Sembe; Arifin, Samsul; Putra, Arif Rachman (Metromedia, 2024)
Organizational culture has become an important element to determine the success of organizations in various sectors. This research aims to analyze the relationship between organizational culture and organizational performance through a comprehensive literature review. With reference to key theories such as Schein's model, Denison, and Barney's competitive framework, this study explores the influence of culture on innovation, employee engagement, and adaptation to changes in the business environment. The analysis shows that a strong organizational culture that is relevant to operational needs can improve performance through various mechanisms, such as strengthening organizational identity, encouraging innovation, and building collaborative relationships across departments. However, challenges such as resistance to change, cultural gaps, and external pressures add complexity to managing organizational culture. Across sectors, culture performs different strategic functions, from driving efficiency in manufacturing to strengthening the culture of innovation in the technology sector. This research concludes that organizational culture becomes an internal element, and a strategic tool to achieve sustainable competitive advantage. Organizations that are able to leverage their culture adaptively and innovatively have a greater chance of surviving and thriving in the global market.